Information technology in librarianship [electronic resource] : new critical approaches - Buschman, John; Leckie, Gloria J. (Libraries Unlimited, 2009)
The ground - both in terms of technological advance and in the sophistication of analyses of technology - has shifted. At the same time, librarianship as a field has adopted a more skeptical